A conceptual model of maintaining equivalence in international market research - Jaciow, Magdalena (Konceptualny model zachowania ekwiwalencji w międzynarodowych badaniach rynku, 2019)
This paper focuses on equivalence in international market research and the conditions for maintaining such an equivalence. Equivalence was defined, in the field of research on an international scale, as an attribute of the results of research conducted in a multicultural environment, which guarantees the coherence of measurement models amongst the analysed countries. This attribute is achieved by the apropriateness of the subject-matter of research, sampling design, measurement tools, the process of direct research and the research results in the scope of the analysed countries/cultures. The model for maintaining equivalence described in this paper provides the researchers with knowledge of the conditions for maintaining equivalence in their international market research, and knowledge of the methods and criteria for evaluating data quality and comparability to those who avail themselves of reports and databases concerning foreign markets
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 46-59
Keywords: equivalence; international research; market; research; model; online purchasing; ekwiwalencja; badania międzynarodowe; rynek; badania; zachowania nabywcze online